Graphene, chemically modified graphenes, and two-dimensional layered materials : electrochemical fundamentals and applications - Eng, Alex Yong Sheng (2017)
Graphene, chemically modified graphenes (CMGs), and two-dimensional layered nanomaterials have attracted a huge interest within the electrochemistry community for a wide variety of interesting properties. This thesis first focuses on graphene oxides (GOs) for their characteristic inherent electrochemistry, where differences were observed based on the production route. Secondly, factors that influence the observed heterogeneous electron transfer (HET) on CMG-modified electrodes were studied. Primarily, chemical composition and morphology were found to affect the observed HET rates at reduced graphene and hydrogenated graphene surfaces. Practical applications were also explored, in the enhancement of supercapacitor charge storage capability and fluorescence properties of functionalised GO. Finally, exfoliated transition metal dichalcogenides were also studied as an emerging class of 2D-layered materials which exhibited improved catalysis of the hydrogen evolution reaction, as an important part of the hydrogen economy. As more 2D nanomaterials are made or discovered, the knowledge garnered is invaluable in the search for solutions that these materials may provide.